2021
DOI: 10.1039/d1ma00463h
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recent progress in electrohydrodynamic jet printing in practical printed electronics: focus on the variety of printable materials for each component

Abstract: Printed electronics will be essential in the implementation of next-generation electronic devices, because printing facilitates fabrication of devices on various rigid, thin, or flexible substrates. Inkjet printing enables precise placement...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 173 publications
(271 reference statements)
0
43
0
Order By: Relevance
“…Moghadam showed the solution viscosity increased with the increase of alginate concentration [93]. Kwon et al reported that the droplet diameter decreased when the polymers had high molecular weight [81].…”
Section: Ink Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moghadam showed the solution viscosity increased with the increase of alginate concentration [93]. Kwon et al reported that the droplet diameter decreased when the polymers had high molecular weight [81].…”
Section: Ink Physical Propertiesmentioning
confidence: 99%
“…Jangung Park et al captured time-lapse images of the pulsating liquid meniscus in one cycle. When the voltage is lower than the critical voltage or the flow rate is lower than the minimum flow rate requested for a cone-jet mode, a pulsating jetting behavior can be generated [81]. With the slight increase of flow rate, a spindle-shaped fragment can be generated before a jet.…”
Section: Ehd Printingmentioning
confidence: 99%
“…2 Printed electronic technologies, including inkjet printing, 3,4 roll-to-roll printing, 5,6 screen printing, 7,8 and electrohydrodynamic jet printing 9,10 have been widely used to fabricate functional electronic devices and circuits applied in health, energy, and consumer electronics. 11–17 As an additive manufacturing technology, 18–22 printed electronic technologies have unique advantages, such as less pollution, low-cost, customization, large-scale production, and good compatibility with flexible substrates, 20,21,23–26 which make low-cost, large-scale manufacturing of electronics possible. Notably, printed thin film transistors (TFTs) have been recognized as one of the most basic and indispensable units of printed electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as the demand for flexible displays has increased and direct printing of display products has been attempted, interest in solution processes has drastically expanded [ 1 , 2 , 3 , 4 ]. In display manufacturing, using the solution process, time and cost can be reduced by more than 60% by direct printing at room temperature instead of using a vacuum deposition process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%